Central Monitor Based On Personal Computer Using Single Wireless Receiver - Ahmad Fanani; Bambang Guruh Irianto; Andjar Pudji (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Central monitor is a tool that monitors the patient's condition with several devices into one display on a personal computer (PC). Pulse Oxymetri serves to monitor the state of oxygen saturation in the patient's blood without going through blood gas analysis. This tool uses a wireless delivery system, HC-11 that can transmit data as far as 10 meters without obstruction. This tool uses a finger sensor, an analog signal conditioner and a microcontroller that is processed to produce a percentage value of SpO2 which is then sent through HC-11. The workings of this tool are very simple by entering the finger sensor on the finger and then it will be detected by the finger sensor that will be displayed on the PC. Digital data from the ADC Atmega is received by the personal computer (PC) via Bluetooth HC-011. Furthermore, the data is processed with the Delphi program and displayed on the monitor. Appears on the Delphi application. After measurement, get an error in the SpO2 parameter, the biggest error is 1.02% and get the smallest error 0.8%.